Modular spectrometer for quality assessment of solid-state detector technology - Perevertaylo, V. L.; Zaitsevsky, I. L.; Perevertaylo, A. V.; Shkirenko, E. A.; Kryukov, A. S. (Technology and design in electronic equipment, 2013)
The authors consider application of charge sensitive preamplifiers and spectrometric amplifiers for transformation and amplification of signals of solid state detectors. The factors that determine the energy resolution of the spectrometer path are presented. The article describes the spectrometry technique for p–i–n-photodiodes quality control. The structure of a multipurpose spectrometer system and schematics of its individual components are presented, their features and parameters are specified.